Vision and Violence in Virginia Woolf’s The Waves - Otto, Peggy D. (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2015)
Virginia Woolf describes her artistic goal in The Waves as an attempt to create “an abstract mystical eyeless book.” Yet, in creating her eyeless book, one that eschews a single narrative perspective, Woolf amasses abundant visual details. For each of her six characters, visual images mark significant moments of being. In fact, Woolf emphasizes the characters’ capacity for sight as a vulnerability that allows them to be violated and wounded over and over. This article analyzes connections between visual imagery and themes of violence in the novel to demonstrate how they cohere into an extended metaphor for the ways in which acts of looking can elicit powerful emotions that threaten to fragment individual identity in painful ways. While Woolf’s novel has received critical commentary that focuses on the role of vision in the narrative and critics have also noted how violence in the text supports other themes, the explicit relationship between sight and violence has not yet been fully explored. A close examination of the visual imagery in key scenes of the novel demonstrates how Woolf engages the reader to participate in the characters’ deepening sense of fragmentation as they are repeatedly assaulted by experience, as the eyes themselves become symbols of the twin dynamics of desire and destruction.